2001
DOI: 10.1007/s002100100444
|View full text |Cite
|
Sign up to set email alerts
|

Conditionally expressed Gα 15 couples to endogenous receptors in GH 3 cells

Abstract: The mammalian G proteins G15 and G16 couple a wide variety of receptors to phospholipase C (PLC) in co-transfected systems, and it has been suggested that they can be used as tools in agonist-screening systems. Using the reversed tetracycline-controlled transactivation system we generated rat pituitary GH3 cell clones that expressed Galphal5 and Galpha16 conditionally to study the coupling of endogenous receptors to both G proteins. In cells expressing moderate levels of Galpha15, activation of various endogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Kotani et al [29] and Wacker et al [35] demonstrated that KISS1R can also couple to Gα 15/16 and thereby generate inositol trisphosphate (IP3) which mobilizes intracellular Ca 2+ . This finding was not surprising given that Gα 15/16 promiscuously couples a large number of GPCRs to phospholipase Cβ (PLCβ) activation and PIP2 hydrolysis [36,37]. Gα 14 has also been reported to couple some Gα i - and Gα s -coupled receptors to PLCβ activation [38]; however, promiscuous coupling by Gα 14 does not appear to be as widespread as that displayed by Gα 15/16 .…”
Section: Kp Signals Via Kiss1r and Gαq/11mentioning
confidence: 92%
“…Kotani et al [29] and Wacker et al [35] demonstrated that KISS1R can also couple to Gα 15/16 and thereby generate inositol trisphosphate (IP3) which mobilizes intracellular Ca 2+ . This finding was not surprising given that Gα 15/16 promiscuously couples a large number of GPCRs to phospholipase Cβ (PLCβ) activation and PIP2 hydrolysis [36,37]. Gα 14 has also been reported to couple some Gα i - and Gα s -coupled receptors to PLCβ activation [38]; however, promiscuous coupling by Gα 14 does not appear to be as widespread as that displayed by Gα 15/16 .…”
Section: Kp Signals Via Kiss1r and Gαq/11mentioning
confidence: 92%
“…Exogenous Ga15 expression at physiological levels (promoted by a tetracycline-induced transactivation system) exerted a similar effect by blunting the Ca 2C transient induced through the Gq/11-coupled thyrotropin-releasing hormone receptor (Offermanns et al 2001). G15 expression also inhibited the signaling of b2AR to Gs (Innamorati et al 2009).…”
Section: G15 Sensitivitymentioning
confidence: 94%
“…-dependent (Offermanns et al 2001) or independent (PKCm in COS cells unpublished) PKC isoforms triggers several pathways, including those stimulating NFkb (Yang et al 2001), ERK , JNK (Heasley et al 1996) JAK (Lo & Wong 2006, Lo et al 2008, cSrc (Lee et al 2009). Small GTPases, such as Ras and Rho are indirectly modulated by G15, via TPR1 (Yu et al 2008, Su et al 2009) and p63RhoGEF (Yeung & Wong 2009) respectively.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…Although Gα15 and Gα16 are clearly more promiscuous than Gα14 [82], they cannot be considered as truly universal [76]. Gα15, in fact, appears to be slightly more promiscuous than Gα16 [32,97]. Interestingly, most of the GPCRs that fail to interact with Gα16 are Gi-selective [for a comprehensive list see refs in 76,98,99].…”
Section: Naturally Promiscuous Gα14 Gα15 and Gα16 Proteinsmentioning
confidence: 98%